Sultat wali al-amr fi taqyid sultat al-qadi - al-Marzuqi, Muhammad ibn Abd Allah ibn Muhammad (al-Riyad : Maktabat al-'Ubaykan, 2004)
Justice, Administration of (Islamic law); MA thesis.
Includes bibliographical references (pages 391-429) and indexes.
Keywords: Judges (Islamic law); Justice, Administration of (Islamic law)